Genetic polymorphism of merozoite surface protein-3 in Myanmar Plasmodium falciparum field isolates - Hương Giang Lê; Thị Lam Thái; Jung-Mi Kang; Jinyoung Lee; Mya Moe; Tuấn Cường Võ; Haung Naw; Moe Kyaw Myint; Zaw Than Htun; Tong-Soo Kim; Ho-Joon Shin; Byoung-Kuk Na (Malaria Journal, 2020)
Abstract Background Plasmodium falciparum merozoite surface protein-3 (PfMSP-3) is a target of naturally acquired immunity against P. falciparum infection and is a promising vaccine candidate because of its critical role in the erythrocyte invasion of the parasite. Understanding the genetic diversity of pfmsp-3 is important for recognizing genetic nature and evolutionary aspect of the gene in the natural P. falciparum population and for designing an effective vaccine based on the antigen. Methods Blood samples collected from P. falciparum-infected patients in Naung Cho and Pyin Oo Lwin, Myanmar, in 2015 were used in this study. The pfmsp-3 was amplified by polymerase chain reaction, cloned, and sequenced. Genetic polymorphism and natural selection of Myanmar pfmsp-3 were analysed using the programs DNASTAR, MEGA6, and DnaSP 5.10.00. Genetic diversity and natural selection of the global pfmsp-3 were also comparatively analysed. Results Myanmar pfmsp-3 displayed 2 different alleles, 3D7 and K1. The 3D7 allelic type was predominant in the population, but genetic polymorphism was less diverse than for the K1 allelic type. Polymorphic characters in both allelic types were caused by amino acid substitutions, insertions, and deletions. Amino acid substitutions were mainly occurred at the alanine heptad repeat domains, whereas most insertions and deletions were found at the glutamate rich domain. Overall patterns of amino acid polymorphisms detected in Myanmar pfmsp-3 were similar in the global pfmsp-3 population, but novel amino acid changes were observed in Myanmar pfmsp-3 with low frequencies. Complicated patterns of natural selection and recombination events were predicted in the global pfmsp-3, which may act as major driving forces to maintain and generate genetic diversity of the global pfmsp-3 population. Conclusion Global pfmsp-3 revealed genetic polymorphisms, suggesting that the functional and structural consequences of the polymorphisms should be considered in designing a vaccine based on PfMSP-3. Further examination of genetic diversity of pfmsp-3 in the global P. falciparum population is necessary to gain in-depth insight for the population structure and evolutionary aspect of global pfmsp-3.